Copper as an answer on the impact of oxydess stress on the eyes - Kempka, Katarzyna; Kamiński, Piotr; Malukiewicz, Grażyna; Bogdzińska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The eyes are exposed to many factors, that contribute to the deterioration of their condition. These include environmental conditions and the influence of reactive oxygen species ROS and oxidative stress. Research shows, that one of the most important tasks of created in such way state of emergency is maintenance of relative balance between oxidants (contributing to the formation of ROS) and antioxidants (restraining their effect). Some chemical elements, especially copper, play a key role in blocking ROS and are a key response to the detrimental effect of oxidative stress. The paper presents an overview of information on the impact of oxidative stress on the eyes and the defense mechanisms with the participation of copper.
Keywords: copper; reactive oxygen species; antioxidation; eyes; environment